Probability, statistics and random process - Veerarajan, T (Tata Mc-Graw-Hill, 2006)
Probability, statistics and random process / Veerarajan, T. -- New Delhi: Tata Mc-Graw-Hill, 2006 519.2 V419e2 2nd ed. No. of Copies : 1